Highly Efficient Photo‐Reduction of p‐Nitrophenol by Protonated Graphitic Carbon Nitride Nanosheets. Issue 20 (20th September 2018) - Qian, Jiajia; Yuan, Aili; Yao, Chengkai; Liu, Jiyang; Li, Benxia; Xi, Fengna; Dong, Xiaoping
Abstract: Photocatalytic reduction of p ‐nitrophenol to p ‐aminophenol is important because of the high toxicity of p ‐nitrophenol and the wide application of p ‐aminophenol. Graphitic carbon nitride (g‐CN) is an excellent photocatalyst for various photo‐reduction reactions, but inefficient for photo‐reduction of p ‐nitrophenol due to the electrostatic exclusion. In this work, we control the morphology and surface property of g‐CN and achieve significantly enhanced activity. The obtained protonated g‐CN nanosheet (pg‐CNNS) material has positively charged surface that can adsorb p ‐nitrophenolate anions, therefore facilitating the transfer of photo‐generated electrons from catalyst to p ‐nitrophenol. Its reaction rate is 1626 times higher than that of the pristine g‐CN. Besides the surface charge, the morphology of photocatalyst also has important effect on activity, which is demonstrated by the relatively low activity of protonated g‐CN in comparison to pg‐CNNS. The pg‐CNNS photocatalyst has an excellent stability and superior catalytic universality for photo‐reduction of various nitroaromatic compounds. This work does not only expand the application of a well‐known material, but also highlights the importance of understanding photocatalytic mechanism for designing photocatalyst. Abstract : Deep exfoliation : The pg‐CNNS photocatalyst prepared by sulfuric acid exfoliation of g‐C3 N4 possesses 2D ultrathin morphology that is favorable for efficient separation of photo‐excited charges and then fast diffusion to surface of catalyst. Furthermore, plentiful positive charges on surface promote adsorption of p ‐nitrophenolate anions and subsequently rapid reduction of PNP to PAP by photo‐generated electrons. Additionally, the pg‐CNNS has good photocatalytic reusability and superb activity for reduction of other functionalized nitroaromatic chemicals.